2018
DOI: 10.3390/ijms20010001
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Independent Correlations between Bacteria and Dysfunction of Gut, Adipose Tissue, and Liver: A Comprehensive Microbiota Analysis in Feces and Mucosa of the Ileum and Colon in Obese Mice with NAFLD

Abstract: Development of non-alcoholic fatty liver disease (NAFLD) is linked to obesity, adipose tissue inflammation, and gut dysfunction, all of which depend on diet. So far, studies have mainly focused on diet-related fecal microbiota changes, but other compartments may be more informative on host health. We present a first systematic analysis of microbiota changes in the ileum and colon using multiple diets and investigating both fecal and mucosal samples. Ldlr−/−.Leiden mice received one of three different energy-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 60 publications
(68 reference statements)
3
44
0
1
Order By: Relevance
“…In line with the observations in the Farnesoid X Receptor Ligand Obeticholic Acid in NASH Treatment (FLINT) trial [41], we observed in the present study an improvement of FFD-induced lobular inflammation and hepatic fibrosis, while we did not observe an improvement in steatosis. The observed effect of FFD on liver inflammation appears to be more pronounced than that of HFD, which is consistent with observations made earlier in a short-term diet intervention study in young mice using the same diets [14]. Our observation that more inflammatory aggregates were found at 18 weeks of FFD feeding compared to 28 weeks supports the view that hepatic inflammation is dynamic and that advanced stages of NASH may have less inflammation than earlier stages as reported by Koyama and Brenner [42].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with the observations in the Farnesoid X Receptor Ligand Obeticholic Acid in NASH Treatment (FLINT) trial [41], we observed in the present study an improvement of FFD-induced lobular inflammation and hepatic fibrosis, while we did not observe an improvement in steatosis. The observed effect of FFD on liver inflammation appears to be more pronounced than that of HFD, which is consistent with observations made earlier in a short-term diet intervention study in young mice using the same diets [14]. Our observation that more inflammatory aggregates were found at 18 weeks of FFD feeding compared to 28 weeks supports the view that hepatic inflammation is dynamic and that advanced stages of NASH may have less inflammation than earlier stages as reported by Koyama and Brenner [42].…”
Section: Discussionsupporting
confidence: 92%
“…However, for other metabolism-modulating interventions, incretins, peroxisome proliferator-activated receptor (PPAR) modulators, and anti-inflammatory or anti-fibrotic interventions, we expect that the model can be useful. As the Ldlr−/−.Leiden model develops the metabolic context with pronounced and stable hypertriglyceridemia and hyperinsulinemia, displays similar histological characteristics as well as the transcriptomic and metabolomics disease profiles [11] as NASH patients, develops atherosclerosis as well as gut dysfunction and dysbiosis [14], the model can be a valuable asset to study the disease comprehensively and complementary to other NASH models. This study emphasizes the importance of choosing the appropriate combination of model and diet for each research question, as it shows that by adaptations of the dietary constituents, different characteristics critical for human pathogenesis can be emphasized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the highfat/high-sugar diet associated with Western lifestyle has altered the composition and metabolic activity of the human gut microbiome [22]. Such diet-induced changes to gutassociated microbial communities are now suspected of contributing to growing epidemics of chronic illness in the developed world, including obesity [23,24] and NAFLD [7,9,25].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is also not known what drives the differences in the gut microbiome compositions between patients with NAFLD and healthy controls, and how this affects disease state or progression. It has been proposed that the gut microbiome can increase energy uptake and initiate inflammation, two factors contributing a dysfunctional metabolism, 20,26,29,30 but the microbiome might also affect other processes associated with NAFLD such as insulin resistance, and metabolism of bile acids and choline. 31 Some of the first indications of the role of the gut microbiome in accumulation of fat in the liver was found in 1982 when researchers found that treatment with the antibiotic metronidazole after a gastric bypass operation resulted in a reduction in hepatic steatosis.…”
Section: The Role Of the Gut Microbiome And Exercise In Non-alcoholicmentioning
confidence: 99%